3-Hydroxy-3-Phenyl-1-m-Chlorophenyltriazene as Spectrophotometric and Complexometric Reagent in the Determination of Iron(III) - Singh, Nahar; Chauhan, R.S.; K. Gupta, Prabhat (Asian Journal of Chemistry, 2016)
The compounds with common functional group —N(OH)—N=N— are termed as hydroxytriazenes. Proposed hydroxytriazenes was prepared by coupling alkyl or aryl hydroxylamine with an aryl diazonium salt in sodium acetate buffered medium (pH @ 5.0) at 0°C to 5°C. Iron(III) forms a blue colour complex with the reagent 3-hydroxy-3-phenyl-1-m-chlorophenyltriazene (R) at room temperature. The complex is stable up to four hours. The composition of the complex [Fe(III) : R] is found 1:2 at 650 nm at optimum pH 3.1-3.9. The molar absorptivity and Sandell's sensitivity values are 3244 mol-1 dm3 cm-1 and 17.22 ng/cm2 respectively at the working wavelength 650 nm. The Beer's law is obeyed in the concentration range 0.3 - 1.8 × 10-4 M of iron. The standard deviation (10 measurements) for 6.7 ppm of iron was found ±0.053 ppm. The interference studies of 30 diverse cations and anions have also been performed. The same reagent was further used as indicator in the complexometric determination of Fe(III) at different variable conditions in presence of 27 diverse ions and this reagent was used in the determination of Fe(III) as spectrophotometrically and complexometrically in sulphide ore sample.